ADJUDICATING UNDERAGE MARRIAGES AT RELIGIOUS COURTS: A Progressive Collaboration between Judiciary and Health Authority - Nur Mustofa, Kholifatun (Al-Ahwal: Jurnal Hukum Keluarga Islam, 2023)
This paper examines the state policies through the judiciary and health institutions in curbing underage marriage. Furthermore, the article sheds light on the extent to which these efforts are realized in the legal practices of the Religious Courts. Data were gathered by analyzing the decisions of the Religious Courts and supplemented with interviews. This paper argues that the state, through the judiciary, has enacted strict mechanisms via the Supreme Court Regulation Number 5 of 2019 concerning Guidelines for handling marriage dispensation cases. Other efforts have been undertaken by the Ministry of Health by requesting the Supreme Court to instruct all judiciary bodies under its jurisdiction to collaborate with health services or relevant institutions to combat underage marriage. To the author's investigation, there are 14 Religious Courts that have collaborated with the Ministry of Health. Judges in these courts consider recommendation letters as one of the considerations. The judges also exhibit a non-permissive attitude by rejecting applications for marriage dispensation without supplementary documents such as recommendation letters from the health services. This study indicates that state institutions, through the judiciary and healthcare sectors, are making progressive efforts to reduce the prevalence of underage marriage.[Abstrak: Paper ini mengkaji kebijakan negara melalui lembaga kehakiman dan kesehatan dalam menekan pernikahan di bawah umur. Selain itu, artikel ini juga melihat sejauhmana upaya tersebut terrealisasikan dalam praktik hukum di Pengadilan Agama. Data dikumpulkan dengan menelaah putusan-putusan Pengadilan Agama dan dilengkapi dengan wawancara. Paper ini menegaskan bahwa negara melalui lembaga kehakiman mengeluarkan ketentuan mekanisme yang ketat melalui Peraturan Mahkamah Agung Nomor 5 Tahun 2019 tentang Pedoman menangani kasus dispensasi nikah. Upaya lain dilakukan oleh Kementerian Kesehatan dengan cara meminta Mahkamah Agung memberikan intruksi kepada seluruh lembaga kehakiman yang berada dibawahnya untuk melakukan kerjasama dengan dinas kesehatan atau lembaga terkait guna menekan pernikahan di bawah umur. Sejauh penelusuran penulis, ada 14 Pengadilan Agama yang berkolaborasi dengan Kementerian Kesehatan. Hakim-hakim di pengadilan tersebut menjadikan surat rekomendasi sebagai salah satu pertimbangan. Hakim juga menunjukkan sikap yang tidak permisif berupa penolakan permohonan dispensasi nikah tanpa dokumen pelengkap seperti surat rekomendasi dari dinas kesehatan. Kajian ini menunjukkan bahwa lembaga negara melalui kehakiman dan kesehatan melakukan upaya progressif untuk menekan tingkat pernikahan di bawah umur.]